Pengaruh Biaya Produksi dan Biaya Penjualan dalam Meningkatkan Laba Bersih - Aldi Prayoga; Hilda Kumala Wulandari; Anisa Sains Kharisma; Yenny Ernitawati; Nasiruddin (Universitas Muhadi Setiabudi, 2019)
This study aims to examine the effect of Production Costs and Sales Costs on Net Profit. The population in this study is the financial statements of manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2018-2020 period. Based on the purposive sampling method, the number of samples used in this study was 15 company using the IBM SPSS program. The method used in this study was a quantitative method. The analysis carried out in this study is multiple linear analysis using hypothesis testing and classical assumption testing. The results of this study indicate that production costs partially have a significant effect on net profit, sales costs partially a have significant effect on net profit, total production costs and selling costs simultaneously have a significant effect on net profit